Conceptualising public-private partnerships: a critical appraisal of approaches to meanings and forms. Issue 2 (11th July 2016) - Mouraviev, Nikolai; Kakabadse, Nada K.
Abstract : Purpose: The purpose of this paper is to survey various meanings attached to a public-private partnership (PPP) and related aspects in Western literature, and identify commonalities and differences between them. Additionally, the article intends to critically assess conflicting and overlapping views on contractual and institutional PPPs, their forms and models, and draw insights for transitional economies. Design/methodology/approach: The article contrasts and compares views on PPP meanings, forms and models within Western PPP literature, and also draws comparisons with understanding of partnership aspects in the Russian language sources. The paper examines theories underpinning PPPs, builds connections to PPP advantages and drawbacks, and provides critical assessment of net benefits that PPPs may bring along to the society. Findings: The article concludes that future PPP research in transitional countries such as Kazakhstan and Russia, particularly in the area of organisational and power arrangements in partnerships, may delineate new concepts such as government as a guarantor of a PPP project, social significance of a PPP project, and risk management in a country's contextual environment. Originality/value: Research in the field of PPPs in transitional countries such as Russia and Kazakhstan is in its infancy. The paper intends to contribute to the body of knowledge about PPPs by providing detailed account and categorisation of their principal meanings, forms, models, underpinning theories, and drawing insights for future research in transitional countries.